2011
DOI: 10.1001/archgenpsychiatry.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Geometric Patterns Early in Life as a Risk Factor for Autism

Abstract: Context Early identification efforts are essential for the early treatment of the symptoms of autism but can only occur if robust risk factors are found. Children with autism often engage in repetitive behaviors and anecdotally prefer to visually examine geometric repetition, such as the moving blade of a fan or the spinning of a car wheel. The extent to which a preference for looking at geometric repetition is an early risk factor for autism has yet to be examined. Objectives To determine if toddlers with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
374
4
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(445 citation statements)
references
References 63 publications
39
374
4
10
Order By: Relevance
“…Two-yearold toddlers with autism have shown no preference for point-lights biological motion, contrary to typically developing controls [19]. Children with autism showed a preference for geometric patterns of movement rather than for social movement [33]. They will also look less to eyes and face areas and more to body and objects when watching scenes from a movie [34] and, when engaged in semi-naturalistic interaction with a familiar adult, they look significantly less to the face [35].…”
Section: Gaze Abnormalities In Autism: Eye Tracking Studiesmentioning
confidence: 94%
“…Two-yearold toddlers with autism have shown no preference for point-lights biological motion, contrary to typically developing controls [19]. Children with autism showed a preference for geometric patterns of movement rather than for social movement [33]. They will also look less to eyes and face areas and more to body and objects when watching scenes from a movie [34] and, when engaged in semi-naturalistic interaction with a familiar adult, they look significantly less to the face [35].…”
Section: Gaze Abnormalities In Autism: Eye Tracking Studiesmentioning
confidence: 94%
“…A set of recent studies raises the possibility that some of these social behavioral deficits in ASD arise due to deficits in reward system functioning [73][74][75]. This hypothesis is supported by studies that report a lack of social motivation in children with autism [76,77]. One rationale for the social motivation-based account of ASD relies on the following premise: if individuals with ASD do not find social stimuli rewarding, and hence do not attend to them as much as neurotypicals, then they are less likely to exhibit empathy toward them.…”
Section: Autism and Reward Systemmentioning
confidence: 95%
“…The other disorder well known to be associated with severe problems in social interaction is Autism Spectrum Disorder (ASD) and there is already a body of research investigating visual processing of faces ASD. Some eyetracking studies in ASD have shown reduced fixations on socially salient aspects of visual scenes (Noris et al, 2012;Pierce et al, 2011;Riby and Hancock, 2009 ;Rice et al, 2012) and there are reports that individuals with ASD look less at facial features (eyes, nose, 5 mouth) than typically developing peers (Chawarska and Shic, 2009;Pelphrey et al, 2002).…”
Section: How Does Trust Develop In Childhood?mentioning
confidence: 99%
“…Despite being an on-going debate, the fixation bias in ASD has been replicated in a substantial number of studies (Noris et al, 2012;Nadel et al, 2012;Pierce et al, 2011;Riby and Hancock, 2009 ;Rice et al, 2012;Chawarska and Shic, 2009;Pelphrey et al, 2002 ;Dalton et al, 2005;Jones et al, 2008 ;Kliemann et al, 2010;Klin and Jones, 2008;Klin et al, 2002). Thus, it seems that, in contrast with children with ASD, the difficulties experienced by children with RAD are not linked to sampling of facial features but to a problem with specific processing of the very same visual information that is available to typically developed children.…”
mentioning
confidence: 99%